PENGARUH TERAPI BERMAIN FLASHCARD UNTUK MENINGKATKAN INTERAKSI SOSIAL ANAK AUTISME DI PUSAT PELAYANAN AUTIS - Margareta Pratiwi (Universitas Adiwangsa Jambi, 2021)
The purpose of this study was to determine the effect of flashcard play therapy to increase social interaction of children with autism at the Autism Service Center. Characteristics of research subjects include children with autism aged 2-5 years. The number of subjects in this study were 6 children, with additional therapist/teacher informants. The results showed that the eye contact compliance dimension before flashcard therapy had an overall average of 0.333, the average increased to 0.75. The Z value is -2.032 with a significant support of 0.042, these results indicate a significant. In the imitation dimension, the overall average value of 0.315 increased to 0.667. The Z value is -1.363 with the support of a significance of 0.173, these results show no significance. The receptive language dimension had an overall mean score of 0.288, increasing to 0.689. Z is -2.201 with a significance support of 0.028, these results indicate a significant. The expressive language dimension has an overall mean score of 0.250, increasing to 0.583. The Z value is -1.841 with a significance support of 0.066, this result shows that it is not significant. From the results of the study, it can be concluded that playing flashcard therapy has an effect on improving eye contact and receptive language skills but has little effect on imitation and expressive language skills.